2005
DOI: 10.1021/es0502876
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Generation from Artificial Wastewater Using an Upflow Microbial Fuel Cell

Abstract: The upflow microbial fuel cell (UMFC) was developed to generate electricity while simultaneously treating wastewater. During a five-month period of feeding a sucrose solution as the electron donor, the UMFC continuously generated electricity with a maximum power density of 170 mW/m2. To achieve this power density, the artificial electron-mediator hexacyanoferrate was required in the cathode chamber. The power density increased with increasing chemical oxygen demand (COD) loading rates up to 2.0 g COD/ L/day af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
338
2
17

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 696 publications
(364 citation statements)
references
References 22 publications
7
338
2
17
Order By: Relevance
“…Electricity generation from artificial wastewater using an upward flow microbial fuel cell has also been considered [25]. Cylindrical anodes, made of grade 10 and 20 ppi RVC, had a volume of 190 dm 3 .…”
Section: Fuel Cellsmentioning
confidence: 99%
“…Electricity generation from artificial wastewater using an upward flow microbial fuel cell has also been considered [25]. Cylindrical anodes, made of grade 10 and 20 ppi RVC, had a volume of 190 dm 3 .…”
Section: Fuel Cellsmentioning
confidence: 99%
“…A potential limitation on the metabolism for cells closer to the anode surface is lack of electron donor or nutrients due to cells in the outer section consuming these components (He et al, 2005;Marcus et al, 2007;Rabaey et al, 2007;Torres et al, 2008). G. sulfurreducens genes encoding acetate transporters that are more highly expressed when acetate is limiting have been identified (Risso et al, 2008).…”
Section: Transcriptional Analysis Of Outer Versus Inner Members Of Cumentioning
confidence: 99%
“…However, the application of the MEC technology to wastewater treatment requires further research to improve the design and develop inexpensive electrode materials with a high specific surface area, good conductivity, and a high stability. Several anode materials have been recently tested in MECs, including graphite granules, reticulate vitreous carbon, carbon foam, and graphite brush electrodes (Aelterman et al, 2006;Chaudhuri and Lovley, 2003;He et al, 2005;Logan et al, 2007;Zuo et al, 2007). The benefits of three dimensional (3D) anodes, which provide increased surface area for microbial attachment (Aelterman et al, 2008;Logan et al, 2007;Zhang et al, 2011), have been demonstrated by comparing a packed bed of irregular graphite granules with three different thicknesses to a one-dimensional configuration (Di Lorenzo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%